Acclimatization and transplantation of Agave angustifolia Haw. vitroplants in wild conditions - Sánchez, Alfonso; Coronel-Lara, Zelenia; Gutiérrez, Aldo; Vargas, Georgina; Coronado, Martha L.; Esqueda, Martín (Revista Mexicana de Ciencias Agrícolas, 2020)
Agave angustifolia Haw. it has been used in a traditional way in Sonora, for the elaboration of the Bacanora spirituous drink. As a consequence of the legalization of this distillate, wild populations are threatened by overuse. To contribute to this problem, the objective of this study was to evaluate the behavior of A. angustifolia vitroplants during their acclimatization to different substrates and transplantation under wild conditions. Four clonal lines (LC15s, LC26s, LC23b and LC24b) were evaluated in four substrates (control: sand, ‘clay soil’ and gravel (3:1:1); treatment I: peat: control mixture (1:1); treatment II: potting soil: control mixture (1:1) and treatment III: peat: potting soil: control mixture (1:1:1). The transplant site was characterized by analysis of vegetation and physical and chemical soil in situ, while the climate with cartography. These biotic and abiotic characteristics defined the transplantation of 1 000 vitroplants, 250 per clone, in three sections of a hillside with subtropical scrub. Height, number of leaves and cover of the agaves were monitored in a period of 66 weeks. After 60 d, the vitroplants were acclimatized with 100% survival in all treatments. The substrate with the highest content of organic matter favored rooting and root growth. The transplant reached a survival of 84 a 98%, under conditions wild with organic management. The response of the clonal lines was dissimilar during acclimatization and transplantation. The stages of the project were developed between 2009 and 2016.